Pregnancy - Related Pelvic Girdle Pain - Esma Sarıkaya; Saynur Yılmaz; Müyesser Okumuş (Gynecology Obstetrics & Reproductive Medicine)
Pelvic girdle pain has a high incidence during pregnancy. To increase the awareness of the health professionals, we discussed the etiology, presentation, risk factors, risk of recurrence, differential diagnosis and multidisciplinary management of this condition.